In vitro Studies on Stimulation of Gymnemic Acid Production using Fungal Elicitor in Suspension and Bioreactor based Cell Cultures of Gymnema sylvestre R.Br. - and V. Mohana srinivasan, C. Subathra Devi (Recent Research in Science and Technology, 2011)
Gymnemic acids have become a valuable drug in diabetes treatment due to their potent antidiabetic activity. These compounds are extracted commercially from large quantities of Gymnema sylvestre. Since the intact plant contains low concentrations of active compound, plant cell cultures have employed as an alternative to produce large amounts of these secondary metabolites. Moreover using a bioelicitor the secondary metabolite production can be increased. The objective of this study was to develop a rapid system for the enhanced production of gymnemic acid. Aspergillus niger cell extract was used as an elicitor to stimulate the production of secondary metabolite. Comparatively 9 fold increase of gymnemic acid yield was obtained in elicited cultures.